Efeito hepatoprotetor da silimarina (Silybum marianum) sobre a hepatotoxicidade induzida por paracetamol (APAP) em ratos espontaneamente hipertensos (SHR) - Freitag, Abel Felipe (2014)
The aim of this work was to investigate the effect of silymarin on a hypertensive state and the hepatic function alterations in an cetaminophen induced model (APAP) of hepatotoxicity in Spontaneously Hypertensive Rats (SHR). The animals were divided into 6 experimental groups (n=12 each group): (I), normotensive Wistar rats (N) were used as a control group, received a saline solution (NaCl 0,9% , orally); (II), SHR that received a saline solution (NaCl 0,9% , orally); (III) and (IV) , N rats and SHR treated with APAP (3g/kg; orally), respectively; (V) and (VI), N and SHR, pretreated with silymarin (SLM) (200mg/kg, orally) respectively during 7 days before the APAP administration. Twelve hours after APAP administration, all animals were euthanized and the hepatic function was determined by plasmatic biomarkers: alanine (ALT) and aspartato aminotransferase (AST), alkaline phosphatase (ALP), glucose (GLU) and gamma glutamyl transferase (Y-GT). Samples of hepatic tissue were used to determine: the activity of the myeloperoxidase enzyme (MPO), the nitric oxide (NO) production. Indeed, tissue samples were selected for histological examination. The results showed that hepatotoxicity was increased in SHR and N animals (groups III and IV). Thus, SLM treatment reversed all changes observed (groups V and VI). Data were expressed as means ± SEM for each group. The results were statistically analysed by ANOVA (One-way), followed by Tukey's test (p < 0, 05). The results were compared with normotensive animals. None significant differences were observed between the animals SHR and N related to ALT levels, indicating that hypertensive state did not interfere in basal hepatic functions. Although there was a significant increase in the ALT levels for APAP treated animals in both groups, the SLM pre-treatment restored these alterations, ALT: (I) 51.6 ± 1.9 U/L; (II) 57.3 ± 3 U/L; (III) 181.5 ± 18.3* U/L (72%); (IV) 196 ± 23.7* U/L (71%); (V) 65 ± 4.7** U/L (64%); (VI) 83.1 ± 7.9** U/L (58%), p<0.0001; a significant difference in the AST levels was observed between N and SHR groups, increased after APAP treatment. The pre-treatment with SLM reduced the AST levels in N and SHR animals, AST: (I) 74.3 ± 4.2 U/L; (II) 103.5 ± 5 U/L; (III) 189.5 ± 16.2* U/L (61%); (IV) 224.7 ± 23.8* U/L (54%); (V) 113.6 ± 11.9** U/L (40%); (VI) 131 ± 7.9** U/L (42%), p<0.0001. After APAP treatment a significant difference in the ALP levels was observed between the SHR and N, which was nor restored after SLM treatment, ALP: (I) 198 ± 14.9 U/L; (II) 270.4 ± 4.7# U/L; (III) 178.2 ± 6.5 U/L (11%); (IV) 245.3 ± 17.62## U/L (10%); (V) 204.3 ± 33.9 U/L (13%); (VI) 195.3 ± 7.05 U/L (20%), p=0.0015; there was no significant difference on GLU levels between SHR and N groups, in both treatments with APAP or SLM, GLU: (I) 150.4 ± 7.9 mg/dl; (II) 150.4 ± 6.7 mg/dl; (III) 156.4 ± 5.2 mg/dl (4%); (IV) 143.4 ± 10.3 mg/dl (5%); (V) 167.2 ± 3.4 mg/dl (7%); (VI) 167.8 ± 4.8 mg/dl (16%), p=0.17. In the ?-GT levels between SHR and N, none significant difference was verified. However it was observed only for SHR animals when compared to that treated with APAP or SLM Y-GT: (I) 1.94 ± 0.2 U/L; (II)1.85 ± 0.2 U/L; (III)1.55 ± 0.4 U/L (25%); (IV) 4.12 ± 1 U/L* (55%); (V) 1.85 ± 0.2 U/L (19%); (VI) 1.66 ± 0.1**U/L (61%), p=0.01; the inflammatory response was evaluated by the activity of MPO, by the production of NO on the hepatic tissue, by histological analysis and by leukocyte infiltration into hepatic tissue. The leukocyte infiltration and MPO activity were increased after APAP treatment whereas SLM reduced the leukocyte migration in both groups. The MPO activity was similar when compared SHR and N groups, MPO: (I) 0.11 ± 0.02U/L; (II) 0.19 ± 0.03U/L; (III) 0.36 ± 0.03*U/L (69%); (IV) 0.54 ± 0.05*U/L (65%); (V) 0.13 ± 0.04**U/L (64%); (VI) 0.23 ± 0.04**U/L (57%), p<0.0001; the NO production, a free radical involved in the inflammatory process, was similar between SHR and N groups. A significant increase in NO production was observed in these groups after APAP treatment. The treatment with SLM decreased NO contents, suggesting anti-free radical activities and anti-inflammatory of the SLM, NO: (I) 34.9 ± 4.7; (II) 38.5 ± 3.8; (III) 68 ± 9.6* (49%); (IV) 84.5 ± 4.8* (54%); (V) 38.9 ± 2** (43%); (VI) 45.9 ± 3.9** (46%), p<0.0001. Liver injury was assessed using histological studies by hematoxylin and eosin staining. Together, our data indicated that hypertensive state affects significantly in the acetaminophen-induced hepatotoxicity. In additions, SLM by acts reducing the functional and histopathological alterations reduces the APAP-hepatotoxicity; probably due to their effects in the free radical production inducing hepatic injury.